2013
DOI: 10.1590/s0080-623420130000500019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with stroke monitored by home care programs

Abstract: The purpose of this study was to evaluate the patient with a stroke in home treatment, investigating physical capacity, mental status and anthropometric analysis. This was a cross-sectional study conducted in Fortaleza/CE, from January to April of 2010. Sixty-one individuals monitored by a home care program of three tertiary hospitals were investigated, through interviews and the application of scales. The majority of individuals encountered were female (59%), elderly, bedridden, with a low educational level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…Nurses that practice in-home care must be sensitive to client demands and, more so, demonstrate a willingness to teach and an interest in seeking well-being for those under their care. Thus, to take the most advantage of the home environment of patient learning, nurses must assess, project, develop, and implement teaching plans that are unique to each situation (61) . Moreover, health education is noted in this review as an important practice of HC nurses, a practice that helps patients, families, and caregivers to build knowledge and skills (58)(59)(60)(61)(62)(63) , thus ensuring their understanding of the therapy project (5) and continuity of care when the team is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses that practice in-home care must be sensitive to client demands and, more so, demonstrate a willingness to teach and an interest in seeking well-being for those under their care. Thus, to take the most advantage of the home environment of patient learning, nurses must assess, project, develop, and implement teaching plans that are unique to each situation (61) . Moreover, health education is noted in this review as an important practice of HC nurses, a practice that helps patients, families, and caregivers to build knowledge and skills (58)(59)(60)(61)(62)(63) , thus ensuring their understanding of the therapy project (5) and continuity of care when the team is absent.…”
Section: Discussionmentioning
confidence: 99%
“…16 The prevention of falls is performed by identifying the risks of falls such as the use of rubber mats in the bathroom, the use of auxiliary devices, personal assistance, lighting and carpeting, as these topics are fundamental and, if not organized in an effective way, they promote the fall of the patients, harming the process of rehabilitation. 3, In summary, the Nursing interventions directed to the care of the patient involve actions ranging from an evaluation of the individual, such as the performance of activities directed to speech training, gait, voiding habit evaluation and exercise training of the pelvic floor, evaluation of the oral hygiene and assistance directed to the correct positioning of the patient, besides the evaluation of the risks of falls and prevention of a new stroke.…”
Section: Discussionmentioning
confidence: 99%
“…2 Dysfunctions such as anxiety, depression, sleep and sexual function disorders, motor, sensory, cognitive and communication disorders are prevalent changes in patients affected by stroke. [2][3][4] Such a situation makes them dependent on Nursing interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that between 30 and 40% of stroke survivors develop some degree of functional dependence, which prevents them from reintegrating into the labor market and demand some kind of assistance in performing basic activities of daily living (ADLs) (5) . A study conducted with patients in the rehabilitation phase identified the location of the injury, recovery time, performance in instrumental activities of daily living and age were the most important determinants of quality of life of patients (6) .…”
Section: Introductionmentioning
confidence: 99%